The Impact of FDI and Economic Growth on Environmental Damage in Member Countries of the Organization of Islamic Cooperation - Muhammad Fadhlan Shiddiq; Taosige Wau (Department of Development Economics, Universitas Sriwijaya, 2022)
Global warming due to environmental damage is a serious problem for all countries in the world. The aim of this research is to analyze the impact of FDI and economic growth on environmental damage and to test the existence of the environmental Kuznets curve in Organization of Islamic Cooperation (OIC) member countries. This research uses secondary data that is a panel, consisting of 57 OIC member countries as a cross-sectional unit from 1998-2020. The data analysis method used in this research is a panel regression model with a fixed effect model (FEM) estimation method approach. This research found that foreign direct investment and economic growth have positive impacts and significant on environmental damage. This research also found that the environmental Kuznets curve hypothesis is also proven to exist in 57 OIC member countries. The policy implication that must be carried out is that the governments of OIC member countries must ensure that FDI which enters the country is FDI that uses environmentally friendly technology so that this FDI is not only good for the economy, but also good for the environment. Economic growth in society must also be accompanied by the increase of public awareness on the environment. This can be achieved through improvements in education. In this way, economic growth will have a good impact on the environment.